Case report: Report of a rare encounter: metastasis of renal cell carcinoma to the thyroid - Xu, Siyi; Xu, Jiawei; Yu, Chengdong; Zeng, Ying; Tang, Lei; Tang, Mu; Yu, Tenghua; Sun, Zhengkui; Zhang, Xiaofang (Frontiers in Oncology, 2024)
Renal cell carcinoma (RCC) is the most common renal tumor, with lung, bone, and liver being the primary sites of metastasis. Thyroid metastasis, on the other hand, is relatively uncommon. Metastatic tumors in the thyroid gland typically manifest as multiple or isolated nodules, which can be easily overlooked due to the lack of specific clinical and imaging features. However, the identification of thyroid metastasis suggests the presence of systemic metastasis and is indicative of a poor prognosis for patients. In this paper, we present two cases of thyroid metastasis following nephrectomy, with the objective of enhancing understanding among medical community regarding the diagnosis and treatment of thyroid metastasis originating from renal cell carcinoma. By raising awareness about this phenomenon, we emphasize the importance of early detection and diagnosis to improve patient prognoses. The implementation of standardized treatment protocols at the earliest possible stage is also emphasized. Through this research, we aim to contribute to the early identification and management of thyroid metastasis in patients with renal cell carcinoma, ultimately leading to improved outcomes.